2012
DOI: 10.1007/s00026-012-0164-3
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Distributions for the Number of Inversions in Labelled Tree Families

Abstract: We consider so-called simple families of labelled trees, which contain, e.g., ordered, unordered, binary and cyclic labelled trees as special instances, and study the global and local behaviour of the number of inversions. In particular we obtain limiting distribution results for the total number of inversions as well as the number of inversions induced by the node labelled j in a random tree of size n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…where the constant κ depends on the particular tree family, i.e., on the degree-weight sequence, and is given in [64]. Consequently, an application of Lemma 2 and taking into account Example 3 yields the following result, which adds to the results of [64] the characterization of the limiting distribution as a mixed Poisson distribution. Corollary 6.…”
Section: The Number Of Inversions In Labelled Tree Familiesmentioning
confidence: 91%
See 3 more Smart Citations
“…where the constant κ depends on the particular tree family, i.e., on the degree-weight sequence, and is given in [64]. Consequently, an application of Lemma 2 and taking into account Example 3 yields the following result, which adds to the results of [64] the characterization of the limiting distribution as a mixed Poisson distribution. Corollary 6.…”
Section: The Number Of Inversions In Labelled Tree Familiesmentioning
confidence: 91%
“…We discuss several families of random trees where a mixed Poisson law arises as the limit law of a discrete random variable X n,j . The parameter n ∈ N usually measures the size of the investigated trees, and j denotes an additional parameter measuring or marking a certain aspect of the combinatorial structure, i.e., a node with a certain label j of interest, often satisfying a natural constraint of the type 1 ≤ j ≤ n, see [47,49,51,64]. In the limit n → ∞, with j = j(n), phase transitions were observed according to the relative growth of j with respect to n, e.g., j = 1, 2, .…”
Section: Examples and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…While analysing linear probing hashing, Flajolet, Poblete and Viola [23] noticed that the numbers of inversions in Cayley trees with uniform random labelling converge to an Airy distribution. Panholzer and Seitz [46] showed that this is true for conditional Galton-Watson trees, which encompass the case of Cayley trees.…”
Section: Inversions In a Fixed Treementioning
confidence: 93%